A decision support tool for the conservation of tropical forest and nearshore environments on Babeldaob Island, Palau - Povak, Nicholas A.; Giardina, Christian P.; Hessburg, Paul F.; Reynolds, Keith M.; Salter, R. Brion; Heider, Chris; Salminen, Ed; MacKenzie, Richard (Forest ecology and management, 2020)
•Developed a decision support tool (DST) to improve nearshore environments in Palau.•DST prioritized catchments to protect forest and reduce grassland-savanna coverage.•Modeled sediment was lowest for forest coverage > 80% and highest for > 40% savanna.•DST identified 57 km2 of high reforestation priority, mostly near coastal towns.•Access limitations may preclude management activities in the island’s interior. Nearshore ecosystems (e.g., mangrove forests, sea grass beds, coral reefs) are some of the most biologically diverse and ecologically productive on Earth, while providing essential goods and services to human communities. Because these ecosystems are subject to threats from both land and sea, their conservation and management requires a ridge to reef approach. Here, we developed a watershed decision support tool (DST) for Babeldaob Island, Republic of Palau, aimed at prioritizing catchments for reforestation of fire degraded savanna or protection of native forest against conversion to savanna. We use a distributed hydrology model to estimate catchment-level sedimentation and water yield for three vegetation scenarios: (1) current vegetation; (2) a hypothetical fully-forested Babeldaob Island; and (3) a hypothetical Babeldaob Island that has been fully converted to savanna. Using the DST, we integrated model results with geospatial information on treatment cost, efficacy, and conservation value to identify where reforestation and forest protection investments would provide the greatest benefits to coral reef health. Modeled sediment yields were lowest for catchments with > 80% tropical forest cover and highest for those with < 40% forest cover. Sediment hotspots were concentrated near coastal population centers. Modeled catchment-level groundwater recharge showed high variability across vegetation scenarios with no clear relationship was identified between recharge and percentage land cover in forest or savanna. The DST identified 14% of catchments as high priority for reforestation of grassland-savanna, and 11% of catchments for protection of native tropical forest. Most high priority reforestation catchments were located near the coast, while all high protection areas were further inland. Results from the DST suggest that road access and slope will not limit reforestation, but the remoteness of inland high priority catchments may limit protection efforts.